Classroom Teacher Strategies for Addressing Disruptive Behavior in an Islamic Elementary School - Thomas Wira Jaya; Firma Andrian (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Metro, 2026)
Disruptive behavior during lessons not only disrupts the learning atmosphere but also hinders student development. This study aims to examine the strategies employed by the class teacher to address student disruptive behavior and to identify the underlying factors—considering gender differences—among third-grade students (Class III D) at Madrasah Ibtidaiyah Negeri (MIN) 2 Metro. A descriptive qualitative approach was used, involving ten informants. Data were collected through interviews, observation, and documentation, while data validity was verified via triangulation of techniques, sources, and time. All data were analyzed through the stages of reduction, presentation, and conclusion drawing. The results indicate that the teacher employs preventive strategies—such as establishing classroom rules—to preemptively curb disruptive behavior, as well as reactive strategies—including reprimands, seat reassignments, physical and verbal punishments, and adjustments to teaching methods—when such behavior occurs. Student disruptive behavior is influenced by internal factors (e.g., hyperactivity, susceptibility to being easily bored, a need for attention, curiosity, and academic difficulties) and external factors (e.g., classroom dynamics and peer influence). Furthermore, male students exhibit higher levels of disruptive behavior across all categories compared to female students. The study concludes that the management of disruptive behavior among Class III D students at MIN 2 Metro remains reactive and focused on situational control.